Towards ontological engineering: A process for building a domain ontology from scratch in public administration - Brusa, Graciela (2008)
The state reformation that took place in the 1990s and the technological explosion have led governments to reframe their way of working so as to be able to offer new and better services for citizens. To achieve this goal, major obstacles must be overcome, such as the problem of semantic heterogeneity that leads to more difficult recovery and integration of information from different government sectors. Although in the private sector solutions to this problem through the building of ontologies have already been set out, the characteristics of government itself have led the direct application of these practices to fail. This paper presents a process for building a domain ontology in the public sector from scratch. In addition, it presents the application of this process for building an ontology for the Budgetary Domain of Santa Fe Province (Argentina).